Researching Otherwise (gta Verlag, 2024)
Methodological, epistemic, and ontological borders have long prevented landscape and urban studies from engaging in transdisciplinary dialogue, sensuousness, and affect. “Researching Otherwise” uncovers possibilities for deploying sensory, collaborative, and restitutive methodological tools to craft spaces for producing knowledge from pluriversal worlds. These methods connect researchers and their objects of investigation in new ways to empower restitutive and regenerative futures “otherwise.” Original contributions stem from research methods based on drawing, photography, sounding and listening, filmmaking, walking, and cartography. They reveal journeys of specialists and their companions while navigating through multi-species walks, engaging in cinematic and performative ways of knowing, submerging in ocean worlds, unsilencing bank vaults and troubled architectural histories, and exploring collaborative ethnographic investigations with refugees.